2013
DOI: 10.1590/s1679-45082013000200016
|View full text |Cite
|
Sign up to set email alerts
|

Isolated rupture of the gallbladder following blunt abdominal trauma: case report

Abstract: Gallbladder rupture following blunt abdominal trauma is a rare event recognized on evaluation and treatment of other visceral injuries during laparotomy. Isolated gallbladder rupture secondary to blunt abdominal trauma is even more uncommon. The clinical presentation of gallbladder injury is variable, resulting in a delay in diagnosis and treatment. We report the case of a patient who suffered an isolated gallbladder rupture due to blunt abdominal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Its overall incidence rate goes from 0.8% to 2.1% in patients with some type of abdominal trauma. (4) The presence of sterile bile in the peritoneal cavity causes discrete irritation, which would explain the slow progression of the disease. (5,6) The diagnosis of gallbladder perforation is confirmed with exploratory laparotomy being more severe damage to the organs overlapped to it.…”
Section: Discussionmentioning
confidence: 99%
“…Its overall incidence rate goes from 0.8% to 2.1% in patients with some type of abdominal trauma. (4) The presence of sterile bile in the peritoneal cavity causes discrete irritation, which would explain the slow progression of the disease. (5,6) The diagnosis of gallbladder perforation is confirmed with exploratory laparotomy being more severe damage to the organs overlapped to it.…”
Section: Discussionmentioning
confidence: 99%
“…In a study which involves 5670 cases of blunt and penetrating trauma reported the incidence of gallbladder trauma (not isolated) to be 1.9% (3) The gallbladder is anatomically protected by the liver, omentum, and other intestinal organs, shielded by the rib cage. 4 The gallbladder damage is usually associated with the additional surrounding visceral injury.5 In a review of 22 patients of gallbladder injury, there was no isolated lesion. 6 The liver lacerations are the most commonly seen injuries with gallbladder injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentations are highly vague with unspecific right hypochondrial pain and can range from an acute abdomen to a slow progression of abdominal symptoms. This can lead to a late diagnosis or delayed surgery several weeks after trauma [ 6 , 15 , 16 ]. When the gallbladder perforates, bile with/without blood extravasates into the peritoneal cavity leading to bile peritonitis which makes diagnosis difficult and causes a delay in treatment [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade hepatic injuries accompanied by pericholecystic, perihepatic, and free fluid may mask gallbladder rupture [ 17 , 19 ]. Occasionally, CT can only depict peritoneal fluid but may not identify the source [15] .…”
Section: Discussionmentioning
confidence: 99%